Documenting diversity in the Amazonian butterfly genus Bia (Lepidoptera, Nymphalidae) - Penz, Carla M.; Casagrande, Mirna M.; Devries, Phil; Simonsen, Thomas J. (Zootaxa, 2017)
A comparative study of over 1,000 specimens allowed us to revise the taxonomy of the Amazonian butterfly genus Bia. We redescribed the genus, and used a selected set of characters to define and describe new species and subspecific taxa. We found that male genitalia showed little variation among taxa, and that wing and genitalia characters varied independently across the range of the genus. We also noted that species diversification seems to follow a north-south Amazonian divide, with Bia actorion and decaerulea occupying the northern portion of the genus range while the remaining four species are found in southern Amazonia. As defined here Bia includes six species: B. actorion (Linnaeus), B. actorion ecuatoria DeVries & Penz, NEW SSP., B. actorion occulta Casagrande & Penz, NEW SSP., B. decaerulea Weymer STAT. NOV., B. decaerulea cayana Simonsen & Penz, NEW SSP., B. decaerulea pallida Casagrande & Penz, NEW SSP., B. rebeli Bryk STAT. NOV., B. rebeli aegina Penz & Simonsen, NEW SSP., B. rebeli acreana Casagrande & Penz, NEW SSP., B. rebeli arikeme Penz & Casagrande, NEW SSP., B. rebeli pareci Penz & DeVries, NEW SSP., B. rebeli cuprea Penz & Casagrande, NEW SSP., B. rebeli tapajos Penz & Simonsen, NEW SSP., B. caelestis Penz & DeVries, NEW SP., B. pucallpa Casagrande & Penz, NEW SP., and B. peruana Röber.